Reduction of the dead region for edge on strip detector by a guard ring structure. - Dejun Han (IEEE Transactions on electron devices)
p-i-n structures and high-resistivity silicon crystals are frequently used for silicon radiation detectors. The depletion layer of the reversed biased pn junction spreads vertically to the back side of the detector while it spreads laterally to a distance comparable to the thickness of the wafer during operation. As a result, a volume of nonactive silicon has to be introduced at the periphery of the active region of the detector. The distance between the edge of the wafer and the ends of the strips, or the so-called "dead region," can pose serious problems to the use of strip detectors in "edge on" configurations for soft X-ray applications. It may also degrade the resolution at abutting detector edges for detectors that are pieced together by multiple detectors. In this paper, a guard ring structure has been introduced in a 1 × 8 "edge on" silicon strip detector. The guard ring is biased at the same potential as the strip p-n junctions. It has been demonstrated that the length of the "dead region" of the "edge on" strip detector can be dramatically reduced without significant increase in the leakage of current in the detector.